RE- DESCRIPTION OF THE NEW SPECIES FOR IRAQ, Asiopertha nazarena MARSEUL, 1878 (COLEOPTERA: SCARABAEIDAE, RUTELINAE) FROM KURDISTAN REGION OF IRAQ - KHIDHIR, ABDUL- QADIR S.; MUSTAFA, REBWAR A. (Journal of Duhok University, 2020)
Depending on specimens deposited in the Insect Museum- Directorate of Agriculture Researches, Ministry of Agriculture & Water Resources- Kurdistan Region- Erbil- Iraq , a re- description of the new species for Iraq, Asiopertha nazarena Marseul, 1878 (Coleoptera: Scarabaeidae) was done. A detailed description of adults were presented and the important body parts such as mouthparts, antenna and male genitalia were photographed. All dates and collection locations were mentioned.